2019
DOI: 10.1024/0300-9831/a000469
|View full text |Cite
|
Sign up to set email alerts
|

1.25 Dihydroxyvitamin D3 Attenuates Hypertrophy Markers in Cardiomyoblast H9c2 Cells: Evaluation of Sirtuin3 mRNA and Protein Level

Abstract: Abstract. Background: The cellular and molecular mechanisms of cardioprotective effects of Vitamin D are poorly understood. Given the essential role of sirtuin-3 (SIRT3) as an endogenous negative regulator of cardiac hypertrophy, this study was designed to investigate the effect of 1, 25-dihydroxyvitamin D3 (calcitriol) on hypertrophy markers and SIRT3 mRNA and protein levels following angiotensin II induced - hypertrophy in cardiomyoblast H9c2 cells. Methods: Rat cardiomyoblast H9c2 cells were treated for 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…VD3's effects on NM‐induced SOD2 inhibition, mtROS generation, and NLRP3 inflammasome activation were blocked in keratinocytes treated with 3‐TYP or SIRT3 siRNA and in skins from SIRT3 −/− mice. Previously, no effect of VD3 on SIRT3 expression in cardiomyoblast H9c2 cells was reported 52 . Herein, we found that VD3 attenuated NM‐induced cutaneous inflammation by activating SIRT3 in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…VD3's effects on NM‐induced SOD2 inhibition, mtROS generation, and NLRP3 inflammasome activation were blocked in keratinocytes treated with 3‐TYP or SIRT3 siRNA and in skins from SIRT3 −/− mice. Previously, no effect of VD3 on SIRT3 expression in cardiomyoblast H9c2 cells was reported 52 . Herein, we found that VD3 attenuated NM‐induced cutaneous inflammation by activating SIRT3 in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 47%
“…Previously, no effect of VD3 on SIRT3 expression in cardiomyoblast H9c2 cells was reported. 52 Herein, we found that VD3 attenuated NM-induced cutaneous inflammation by activating SIRT3 in vitro and in vivo. Although the precise mecha-F I G U R E 8 VD3 ameliorated NM-induced cutaneous inflammation by inactivating the NLRP3 inflammasome through the SIRT3-SOD2-mtROS signaling pathway nisms by which VD3 induces SIRT3 expression and activity remain to be established, our present data indicated that VD3 is a feasible treatment option for NM-induced cutaneous inflammation by inactivating NLRP3 inflammasome, which was partially mediated through the SIRT3-SOD2-mtROS signaling pathway.…”
Section: Discussionmentioning
confidence: 76%
“…For example, VitD may attenuate LVH via counteracting hypertension, thereby suppressing the upregulation of Rac1 GTPase that occurs secondary to the hypertrophy. Moreover, the ability of VitD to directly target the cardiac myocytes [25] , [26] , [19] allows us to speculate that VitD alters the protein level of Rac1 GTPase independent of influence upon hemodynamic parameters, in fact, by a direct effect on cardiomyocytes and suppression of LVH-associated (pro-hypertrophic) factors. Some likelihood also is that VitD reduces the protein level of Rac1 GTPase in hypertrophied cardiomyocytes exclusively via impact on signaling pathways involved in the antioxidant system or those related to the control of survival, i.e., independent of anti- hypertrophy or hypertensive effects.…”
Section: Discussionmentioning
confidence: 99%
“…AAB was performed in conformity with earlier protocols [19] , [37] . In short, after anesthetizing animals with IP injection of a mixture of ketamine (70 mg/g) and Xylazine (10 mg/g), an incision was made in the left flank to rapidly obtain access to the suprarenal abdominal aorta.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation